Assessing protected area overlaps and performance to attain China's new national park system. (January 2020) - Wu, Ruidong; Hua, Chaolang; Yu, Guangzhi; Ma, Jianzhong; Yang, Feiling; Wang, Junjun; Jin, Tong; Long, Yongcheng; Guo, Yang; Zhao, Haiwei
Abstract: Overlapping protected area (PA) designations are a global widespread phenomenon and have seriously deteriorated the performance of China's PA system. However, a comprehensive investigation on the extents of both overlapping designations and conservation complementation among different PA categories is still lacking in China. Here, we used the case of Yunnan, southwest China, to quantitatively assess the spatial and institutional overlaps among six primary PA categories. We then investigated the conservation complementation among the different PA categories by measuring their contributions to improving the ecological representation, coverage of areas of conservation importance, and connectivity of the entire PA network. Overlaps existed within most pairs of PA categories; approximately 10% of the total PA area was designated as multiple categories and simultaneously managed by more than one institution. Different PA categories could complement each other in terms of protection coverage, ecological representation and connectivity. The sustainable use PAs effectively complemented the strict PAs by doubling the total PA coverage, increasing the ecological representation, raising the overall connectivity index from 1.44% to 4.03% and taking 50% of the total area of key connecting PAs. Conflicting management regimes in combination with expanded PA objectives are the major drivers of the overlapping PA designations. By explicitly measuring the extents of overlapping and complementation among different PA categories, our analysis helps to efficiently assess the existing PAs and integrate them into China's new national park system. This study provides insights into empirical generalities about overlapping designations and conservation complementation among multiple PA categories. Highlights: We quantitatively assess overlapping protected area (PA) designations in Yunnan, China. Approximately 10% of the total PA area was designated as multiple categories. Sustainable use PAs were essential to uphold PA coverage and connectivity. Conflicting management regimes were the major drivers of overlapping PA designations. Our study provides evidence-based support for developing China's new national park system.